Pengaruh Kualitas Produk, Kualitas Pelayanan Dan Harga Terdahap Kepuasan Pelanggan Kopikota Bali - Dewiwati Sujadi; I Gede Adi Pratama; Ni Luh Sili Antari Sili (STIE Mandala Jember, 2023)
ABSTRACT This study aims to determine and analyze whether product quality, service quality, and price affect to the customer satisfaction of Kopikota Bali. The data collection technique is purposive sampling. The sampling method was carried out purposively or with certain objectives and considerations with the criteria of customers aged 17 years and over and had made transactions at Kopikota Bali. Respondents were set at 25 x 5 = 125 respondents. The research method applied in this study is based on multiple linear regression analysis with data collection techniques used are documentation and questionnaires. The data analysis technique used is quantitative descriptive analysis, validity and reliability test, classical assumption test, multiple linear regression analysis and t test analysis. The results of the analysis show that the regression results are Y = 1.125 + 0.221X1 + 0.297X2 + 0.476X3. The conclusion obtained is that product quality (X1) has a positive and partially significant effect on customer satisfaction (Y) which is shown in the regression coefficient β1X1 which has a positive value of 0.211 with tcount = 2,301 > ttable = 1,979 with sig = 0,023. Service quality (X2) has a positive and partially significant effect on customer satisfaction (Y) which is shown in the regression coefficient β2X2 which has a positive value of 0.297 with a value of tcount = 4,450 > ttable = 1,979 with a value of sig = 0.000. Price (X3) has a positive and partially significant effect on customer satisfaction (Y) which is shown in the regression coefficient β3X3 which has a positive value of 0.476 with tcount = 4.219 > ttable = 1.979 with sig = 0.000 value. Suggestions for Kopikota Bali are the need to maintain product quality, service quality, and prices provided, and if necessary to be improved again in order to always achieve customer satisfaction. Keywords: Product Quality, Service Quality, Price and Customer Satisfaction